2015
DOI: 10.1093/cid/civ075
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Colonization and Determinants of Earlier Clearance of Colonization With Methicillin-Resistant Staphylococcus aureus

Abstract: With a systematic, regular sampling protocol, duration of MRSA colonization was noted to be shorter than previously reported, although 19.8% of patients remained colonized at 6 months. The association between clindamycin and shorter duration of colonization after MRSA SSTI suggests a possible role for the antibiotic selected for treatment of MRSA infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 36 publications
5
47
1
2
Order By: Relevance
“…However, one study conducted in a rehabilitation center estimated the median nasal carriage time to be 44 days, which is not very different from our estimate (7). Moreover, a recent study that collected specimens from patients with MRSA skin and soft tissue infections and their household members for MRSA surveillance cultures every 2 weeks for 6 months reported median MRSA colonization duration of 21 days, a finding which is also close to our findings (31). Pertinently, fluoroquinolone use in the present study was associated with earlier loss of MSSA colonization but not with loss of MRSA colonization.…”
Section: Discussionsupporting
confidence: 91%
“…However, one study conducted in a rehabilitation center estimated the median nasal carriage time to be 44 days, which is not very different from our estimate (7). Moreover, a recent study that collected specimens from patients with MRSA skin and soft tissue infections and their household members for MRSA surveillance cultures every 2 weeks for 6 months reported median MRSA colonization duration of 21 days, a finding which is also close to our findings (31). Pertinently, fluoroquinolone use in the present study was associated with earlier loss of MSSA colonization but not with loss of MRSA colonization.…”
Section: Discussionsupporting
confidence: 91%
“…Cluzet et al recently published a study to evaluate both colonization duration and predictors of clearance of MRSA colonization. They found that treatment of skin and soft tissue infection with clindamycin was associated with earlier clearance of MRSA colonization (136). Although the use of oral agents in decolonization of patients with S. aureus has been evaluated in several studies, the optimal dose and duration of therapy are still unclear, as well as whether combination therapy is preferred over monotherapy.…”
Section: Oral Agentsmentioning
confidence: 99%
“…The events that follow a CA-MRSA infection in a household include an increase in: (i) the risk of infections among other household members [26, 44, 45, 4851]; (ii) MRSA colonization among other household members [46, 47, 5257, 59]; and (iii) contamination of environmental surfaces [24, 25, 58]. These reports have described epidemic clones that ‘ping pong’ among family members [26, 51], resulting in high rates of recurrent infection.…”
Section: Staphylococcus Aureus Transmission and Disease Within The Homentioning
confidence: 99%